2016
DOI: 10.1177/0267659116670481
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation support for life-threatening acute severe status asthmaticus

Abstract: ECMO could provide adjunctive pulmonary support for intubated asthmatic patients who remain severely acidotic and hypercarbic despite aggressive conventional therapy. ECMO should be considered as an early treatment in patients with status asthmaticus whose gas exchange cannot be satisfactorily maintained by conventional therapy for providing adequate gas change and preventing lung injury from the ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Traditionally, protective mechanical ventilation with rescue therapy, including neuromuscular blockade, has been the mainstay treatment for NFA. However, technical advances in extracorporeal membrane oxygenation (ECMO) have made it a promising alternative therapy in the treatment of life-threatening NFA [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, protective mechanical ventilation with rescue therapy, including neuromuscular blockade, has been the mainstay treatment for NFA. However, technical advances in extracorporeal membrane oxygenation (ECMO) have made it a promising alternative therapy in the treatment of life-threatening NFA [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The low incidence of NFA may preclude large-scale, prospective randomized trials on the effectiveness of ECMO in this context. Nevertheless, an increasing number of reports suggest ECMO may be an effective rescue therapy for NFA [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the conclusions are limited by an inability to compare ECMO to other therapies and limited external validity as the database had included data from an earlier era in which the ECMO technology was not as advanced as it is now. One multicentre European case series of 16 patients of ECMO use in SA had demonstrated good efficacy in improving gas exchange parameters and leading to successful extubation without neurological sequelae in all study patients 19. In addition, there are case reports highlighting application of ECMO for SA in unique clinical scenarios including patients who with plastic bronchitis,20 in the setting of secondary pneumothorax,21 in pregnancy22 and following atracurium administration 23…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they used data from the multicenter Extracorporeal Life Support Organization (ELSO), but included only a small number of patients. In 2017, there was another review of the same database, confirming that the use of ECMO is an acceptable option, and resulted in acceptable survival rates, although it is necessary to understand and reduce the ECMO related complications [280]. Di Lascio et al, using ECMO for asthmatic patients receiving IMV, showed that it could provide adjunctive pulmonary support for patients who remain severely acidotic and hypercapnic despite aggressive conventional therapy [281].…”
Section: Pharmacological and Non-pharmacological Managementmentioning
confidence: 99%